1998
DOI: 10.1055/s-2006-957477
|View full text |Cite
|
Sign up to set email alerts
|

Antiplasmodial and Cytotoxic Metabolites from the Maltese SpongeAgelas oroides(1)

Abstract: From a Maltese sample of the marine sponge Agelas oroides, five compounds: oroidin (1), 2-cyano-4,5-dibromopyrrole (2), 4,5-dibromopyrrole-2-carboxylic acid (3), 4,5-dibromopyrrole-2-carboxylic acid methyl ester (4), and 4 alpha-methyl-5 alpha-cholest-8-en-3 beta-ol (5) have been isolated. For compounds 1-5, completely assigned 1H- and 13C-NMR data are reported for the first time. For 2 a single crystal X-ray crystallographic analysis proved its structure unambiguously. The X-ray analysis of 2 indicated it to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…Other brominated pyrrole alkaloids, especially some of the dimeric molecules, are known to have antibiotic, antiparasitic and cytotoxic effects [9,14,29], interact with membrane ion channel function [30] and therefore ionic trans-membrane transport processes [11] and inhibit cell motility in a variety of cancer cell lines [31]. As sensory and olfactory neurones of predators are primarily exposed to sponge compounds [11] and are equipped with numerous ion channel and cellular signal chains it seems plausible that these alkaloids serve as feeding deterrents as described by several authors [6,7,8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other brominated pyrrole alkaloids, especially some of the dimeric molecules, are known to have antibiotic, antiparasitic and cytotoxic effects [9,14,29], interact with membrane ion channel function [30] and therefore ionic trans-membrane transport processes [11] and inhibit cell motility in a variety of cancer cell lines [31]. As sensory and olfactory neurones of predators are primarily exposed to sponge compounds [11] and are equipped with numerous ion channel and cellular signal chains it seems plausible that these alkaloids serve as feeding deterrents as described by several authors [6,7,8].…”
Section: Discussionmentioning
confidence: 99%
“…For example, sponges are well known to produce a large number of bioactive compounds such as brominated pyrrole imidazoles as feeding deterrents against predatory fishes [6,7,8]. Some brominated pyrrole imidazole alklaloids are known to be cytotoxic [9] and to interact with ion channels and be involved in cellular signalling in mammalian and invertebrate cells [10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…If such a deterrent comprises, beside its unpalatability to the fish, any pharmacological potency was only known in part for oroidin. Oroidin is also present within the tissues of A. clathrodes, A. cervicornis, A. dispar and A. wiedenmayeri (Braekman et al, 1992;Assmann et al, 1999Assmann et al, , 2000Lindel et al, 2000;Assmann et al, in press) and has previously been shown to be cytotoxic (König et al, 1998).…”
Section: Discussionmentioning
confidence: 97%
“…Brominated pyrrole-imidazole alkaloids are known to be fish feeding deterrent against the reef fish Thalassoma bifasciatum [6,7] and demonstrate antibiotic activity [8] even against pathogens like Helicobacter pylori [9]. Especially, the degree of bromination and the guanidine moieties have shown to be important for the alkaloids efficacy to disturb cellular calcium ion entry via voltage operated channels in neuroendocrine cells [10][11][12], which possess mainly L-and N-type calcium channels common in neuronal cells.…”
Section: Introductionmentioning
confidence: 99%